Platform Choices: Impact on Startup Performance - Tejaswi Channagiri Ajit; Mark A. Jamison (International Telecommunications Society (ITS), 2022)
We study the impact of platform choice (iOS vs Android) for firms that build apps for smart phones. We merge app data from Sensor Tower® with financial performance data from Crunchbase®. We find that apps that begin on Android have greater average downloads per month. However, apps with the greatest average downloads per month are likely to have begun on iOS. On each platform, the categories that attracted most app-based firms had greater skewness and kurtosis in average downloads per month. When endogenizing the choice of platform using propensity-score matching, firms that prefer to launch on iOS first seem likelier than those that launch on Android first to not receive any funding at all. However, they seem to receive greater funding in USD per firm.
Keywords: L13; L15; L51; 330; platforms; innovation; competition